Gut microbiota of Brazilian Melipona stingless bees: Dominant members and their localization in different gut regions - Amanda Tristao Santini; Alan Emanuel Silva Cerqueira; Nancy A. Moran; Helder Canto Resende; Weyder Cristiano Santana; Sergio Oliveira de Paula; Cynthia Canedo da Silva (PLoS ONE, 2026)
The gut microbiome of eusocial corbiculate bees, which include honeybees, bumblebees, and stingless bees, consists of anciently associated, host-specific bacteria that play crucial role in nutrition, pathogen defense and host fitness. While the core microbiota of honeybees and bumblebees is well characterized, the composition, spatial organization, and evolutionary dynamics of the microbiota of stingless bees remain poorly understood. This gap is particularly evident in the diverse genus Melipona , where Snodgrassella and Gilliamella , ubiquitous symbionts of honeybees and bumblebees, appear rare or absent, indicating a shift in microbiota composition in these stingless bees. Here, we address this gap by characterizing the microbiota of multiple Melipona species using 16S rRNA amplicon sequencing of newly collected and previously published data from field-collected samples. We also mapped the spatial localization of the dominant microbiota members within the gut regions of Melipona quadrifasciata anthidioides through targeted dissection. The Melipona microbiota is dominated by members of the genera Bifidobacterium , Lactobacillus , Apilactobacillus , Floricoccus , and Bombella , with striking regional structure. Apilactobacillus and Bombella dominate in the crop, whereas Apilactobacillus and other members of the Lactobacillaceae are most abundant in the ventriculus. The ileum lacks Snodgrassella and Gilliamella but contains a putative new symbiont closely related to Floricoccus , as well as strains of Bifidobacterium , Lactobacillaceae (including Apilactobacillus ), and Bombella . The rectum is dominated by Bifidobacterium and Lactobacillus . These findings reveal a distinct microbiota architecture in Melipona that differs from other corniculate bees yet retains compartment-specific specialization, suggesting an alternative symbiotic strategy that may reflect unique dietary ecology and evolutionary history. Understanding these patterns advances our knowledge of host-microbe symbiosis and provides a baseline for microbiome conservation in declining stingless bee populations.